Study on shear performance of cold-formed thin-walled steel walls sheathed by paper straw board. (15th October 2021) - Zhang, Xiuhua; Zhang, Enyuan; Zhang, Yizhuo
Highlights: A new type of CFS wall sheathed with paper straw board is proposed. The characteristic values of the bearing capacity, lateral stiffness, ductility coefficient and energy dissipation coefficient of CFSSB wall are obtained. Factors affecting the shear capacity of CFSSSB composite walls are investigated. A design formula is proposed to predicting shear capacity of CFSSB walls. Abstract: To explore the application of environmental protection material-paper straw board in cold-formed thin-walled steel (CFS) structures and further develop the sheathing system, an innovative CFS framing wall sheathed by paper straw board (CFSSB) is proposed. Eight CFSSB composite wall specimens and one CFS frame without sheathing were tested under monotonic and reversed cyclic horizontal loads to study the shear performance of the CFSSB composite wall. Also, the shear performance of the wall specimens can be obtained. The key parameters include the value of the vertical load and the form of the CFS frame in this experimental program. By analyzing the specimen's failure forms and failure process, the characteristic values of the bearing capacity, lateral stiffness, ductility coefficient and energy dissipation coefficient are obtained. The results show that the existence of paper straw board and adding diagonal braces to the CFS frame can significantly improve the shear capacity of CFSSB composite walls. The favorable seismic performance of the CFSSB composite wall was demonstrated in the experiment. In addition, a finite element model for CFSSB composite wall is developed using the software package ANSYS. The finite element analysis (FEA) results show a good agreement with the experiment results in terms of failure modes and skeleton curves, which verify the feasibility of the FEA model. Furthermore, extensive parametric analysis was carried out to analyze the factors affecting the shear capacity of the CFSSB composite wall. The FEA results show that the spacing of studs and self-tapping screws greatly influences the shear capacity of walls. Moreover, based on the failure of the screw connections, a formula for calculating the shear capacity of the CFSSB composite wall is proposed. The results of the formula calculation show good agreement with the experiment and FEA results, and it can provide a reference for engineering design.